The Impact of Resilience on the Perception of Chronic Diseases From Older Adults\' Perspective - Mahboubeh Rezaei; Fatemeh Sadat Izadi-Avanji; Azadeh Safa; Sílvia Fernanda Cal (Iran University of Medical Sciences, 2018)
Background: Older adults with chronic illnesses face many challenges related to their diseases and need higher resilience capacities to overcome. Resilience, as a mediator among various dimensions of health, can lead to positive health outcomes in such people. The current study aimed at discovering the impact of resilience on the perception of chronic disease from older adults' perspective.  Methods: The current qualitative study was conducted in specialized clinics of Shahid Beheshti Hospital, Kashan, Iran. A total of 25 older adults with chronic diseases were recruited by purposive sampling. Data were generated by semi-structured interviews and continued until data saturation. All interviews were transcribed verbatim and coded by MAXQDA7 software. Data were analyzed based on Graneheim and Lundman approach.  Results: Three main themes were extracted from the data including achieving spiritual transcendence (approaching God, appreciate the beauty around); creating peace and balance (controlling the inner stress, maintaining solidarity of family); overcoming the disease (compliance with treatment, building effective interpersonal relationships). Conclusion: The themes indicated that effective interventions such as teaching stress management, communication skills, and adherence to treatment should be provided by healthcare providers and policy makers to improve the resilience of the older adults with chronic diseases.